The response of firms` investment and financing to adverse cash flow shocks: the role of bank relationships - Catherine Fuss; Philip Vermeulen (European Central Bank (ECB), 2006)
We test whether firms with a single bank are better shielded from loss of credit and investment cuts in periods of adverse cash flow shocks than firms with multiple bank relationships. Our estimates of the cash flow sensitivity of investment show that both types of firms are equally subject to financing constraints that bind only in the event of adverse cash flow shocks. In these periods, firms incur lower cuts in investment expenditures when they can obtain extra credit. In periods of adverse cash flow shocks, the probability of obtaining extra bank debt becomes more sensitive to the size and leverage of the firm.
Keywords: D92; 330; financial constraints; firm financing; firm investment; lending relationships; Fremdkapital; Kreditwürdigkeit; Cash Flow; Schock; Belgien